Incorporating an immunization course in the pharmacy curriculum: Malaysian experience - Al-lela, Omer Qutaiba; Bahari, Mohd Baidi; Elkalmi, Ramadan Mohamed Mahmod; Awadh, Ammar Ihsan Jawad (American Association of Colleges of Pharmacy (AACP), 2012)
To the Editor. The immunization system is a successful systematic program, especially during the last century. However, the immunization system is still imperfect because many countries still have unvaccinated children. The most common reasons for parents not having their child vaccinated are concern about immunization adverse effects, disbelief that the vaccine works, lack of awareness that the immunization is necessary, and lack of healthcare provider recommendation for the immunization.1 Health-care providers play an important role in child immunization because they have positive effects on parental decisions related to immunization.2 As a health care provider, pharmacists have played a role in promoting, maintaining, and improving immunization rates among children because the pharmacist is one of the most accessible healthcare professionals. A pharmacist can be trained to screen children for immunizations and counsel parents on immunization decisions, including providing information on immunizations risks and immunization benefits. In addition, pharmacists are highly regarded by the parents and by most immunization providers as drug information specialists, and often sought by people for medical advice. ......